THE PREVALENCE AND INTENSITY OF CARIES IN CHILDREN WITH HODGKIN'S DISEASE, IT WAS EXAMINED AT DIFFERENT PERIODS OF THEM MANIFESTATION - L.F. Kaskova; I.Y. Vashchenko; N.V. Janko; O.O. Karpenko; N.N. Korotych (Український стоматологічний альманах, 2018)
Total of children with malignant lymphomas has increased for last 15 years. Advances in the treatment regimens, including multiagent chemotherapy and radiation therapy, have greatly increased the chances of survival and achieving remission at 98% patients for first 4 years. The pediatric dentist plays an important role in the prevention, stabilization, and treatment of oral and dental problems that can compromise the child’s health and quality of life during, and follow up of the cancer treatment.